Increasing trends and incidence of nonfatal overdose among women sex workers who use drugs in British Columbia: The role of criminalization-related barriers to harm reduction. (1st March 2023) - Argento, Elena; Shannon, Kate; Fairbairn, Nadia; Moreheart, Sarah; Braschel, Melissa; Goldenberg, Shira
Abstract: Background: Structurally marginalized women who use drugs experience disproportionately elevated health and social inequities that require specialized responses to mitigate risk of overdose. This study aimed to longitudinally investigate incidence and predictors of first nonfatal overdose among women sex workers who use drugs. Methods: Data (2010–2019) were drawn from AESHA (An Evaluation of Sex Workers Health Access), a community-based, prospective, open cohort of > 900 women sex workers in Metro Vancouver, Canada. Incidence was examined and Cox regression modelled time-updated predictors of first nonfatal overdose. Time series analysis examined annual trends. Results: Among 273 eligible participants, 23% (n = 63) reported a first nonfatal overdose over follow-up with an incidence density of 5.87/100 person-years. In multivariable analysis, independent predictors of time to nonfatal overdose were police-related barriers to harm reduction (Adjusted Hazard Ratio [AHR]=2.62; 95% confidence interval [CI] 1.51–4.54), binge alcohol use (AHR=2.28; 95%CI 1.16–4.45), opioid use (AHR=2.23; 95%CI 1.15–4.33), and crystal methamphetamine use (AHR=2.07; 95%CI 1.27–3.39). Time series analysis demonstrated a significantly increasing trend in first nonfatal overdose, with annual proportions increasing 0.59% (95%CI 0.39–0.78%) every year, on average. Conclusions: This study provides strong longitudinal evidence from the longest-standing cohort of sex workers in North America. Nonfatal overdose in this setting is a critical public health concern. Criminalization-related barriers to harm reduction strongly predicted nonfatal overdose. Structural changes to legal and policing practices alongside gender-sensitive addiction services are urgently needed. Highlights: There was a high incidence of nonfatal overdose among sex workers who use drugs. Time series analysis shows significant increasing trend in first nonfatal overdose. Criminalization-related barriers to harm reduction strongly predicted overdose. Structural changes to legal and policing practices are urgently needed.